The Law of Guardianship in Marriage According to Madhhab Scholars - Muhammad Tang; Nilfatri (Zabags Qu Publish, 2025)
Guardianship in the marriage contract is one of the key elements in Islamic marriage law and serves as a main differentiator between the views of various scholarly schools of thought (madhhabs). The presence of a guardian (wali) is seen as a form of protection for women in a sacred contract that has significant implications for marital life. This article examines the views of the four major Islamic legal schools—Hanafi, Maliki, Shafi’i, and Hanbali—on the legal status of the wali in marriage, including the form and conditions of guardianship, as well as the legal consequences if a marriage contract is conducted without a wali. Using a literature review methodology on classical and contemporary texts, this study finds a significant difference between the Hanafi madhhab, which allows adult women to marry without a wali, and the other madhhabs, which require the presence of a wali for the validity of the marriage contract. These differences arise not only from divergent legal reasoning but also from differing views on women's autonomy and the concept of protection in Islamic law. This study highlights the importance of understanding madhhab differences as a rich source of Islamic legal heritage, as well as the urgency of ijtihad in responding to contemporary social and legal needs.